A STUDY ON MOBILE PHONE USE IN CIVICS EDUCATION LEARNING AT SMP NEGERI 22 SAMARINDA - Alya Nur Fitriani; Aloysius Hardoko; Marwiah Marwiah; Endang Herliah (SOSIOEDUKASI, 2025)
This study discusses the use of handphone in the teaching and learning process of Pancasila and Civic Education (PPKn) by teachers at SMP Negeri 22 Samarinda. This study uses a descriptive qualitative approach with data collection tecniques through observation, interviews, and documentation. The results show that the use of handphone in PPKn laerning covers three main aspects, namely positive impacts, negative impacts, and challenges. On the positive side, the use of handphone can increase students’ motivation to learn, independence, and digital literacy skills. Handphone also make it easier for students to search for information, broaden their knowledge, and understand the material in an interesting and contextual way. In addition, the use of handphone supports active, creative, and collaborative learning between teachers and students. However, the negative impact that arise include misuse for non-academic activities, decreased concentration in learning, and technical obstacles such as limited internet network and battery power. The challenge for Civic Education teachers is to control the us of handphone so that it remains in line with learning objectives and to address differences in technological capabilities among students. To overcome this, teachers implement supervision, educational sanctions, and character building in discipline and responsibility with the support of the school and parents.